Oxidation and silanization of MWCNTs for MWCNT/vinyl ester composites (eXPRESS Polymer Letters)
Chemical functionalization of multi-wall carbon nanotubes (MWCNTs) is conducted by means of acid oxidation, direct silanization of the as-received MWCNTs and a sequential treatment based on oxidation and silanization. Polymer composites made from the functionalized MWCNTs and a vinyl ester resin are fabricated and tested in compression. It is found that although silanization could be achieved without the assistance of a previous oxidative treatment, oxidizing the MWCNTs by HNO3/H2O2 prior to silanization yields significantly better attachment of the silane molecules to the CNT surface and hence, better mechanical performance of the resulting composite. The limited improvements in mechanical properties found are discussed in light of the reduction of the nanotube length after MWCNT oxidation and composite processing.